UPAYA MEMBANGUN CITRA MEREK MELALUI KEPUASAN KONSUMEN BERDASARKAN KEUNGGULAN PRODUK DAN KEUNGGULAN LAYANAN (STUDI EMPHIRIS PADA PT INAX INTERNATIONAL) - Fandhy Akhmad S, 11.4202.0005 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study is intended to company PT Inax International sanitary ceramics in order to determine the level of excellence of a product, service excellence, customer satisfaction and quality brand image in order to create a quality product that always remain competitive in the current era of globalization and which will future. These results indicate that, (a) shows the advantages of the partial products have a significant effect on consumer satisfaction, (b) service excellence partial significant effect on customer satisfaction, (c) customer satisfaction partially significant effect on brand image (d) product excellence partially significant effect on the image of the brand (e) product excellence and service excellence together simultaneously significant effect on customer satisfaction (f) consumer satisfaction and product excellence together persial sumultan significant effect on brand image brand Keyword : Excellence of product, excellence of service, satisfaction of consumer  and brand image